Systemic expression of genes related to inflammation and lipid metabolism in patients with dyslipidemia, type 2 diabetes mellitus and chronic periodontitis - Nepomuceno, Rafael [UNESP] (2019)
Inflammatory diseases, as periodontal disease (PD), has been associated with disturbance of lipid and glycemic metabolisms, as demonstrated by the increasing of PD patients with type 2 diabetes mellitus (T2D) and/or dyslipidemia comorbidities. We aimed to investigate the expression of inflammation and lipid metabolism genes, and correlations among clinical and biochemical characteristics in normoglycemic or T2D patients with dyslipidemia and PD, in comparison with healthy individuals. Five groups of 30 individuals each (150 patients) were formed based upon T2D, dyslipidemic and periodontal status. Blood analyses of lipid and glycemic profiles were carried out, and the gene expression was assessed by RT-qPCR. The systemic expression of IL6, TNFA and LEP genes were significantly higher in T2D, dyslipidemia and PD patients, while the PECAM1 gene showed the opposite. Higher RETN levels were found in patients with T2D independently of their glycemic control status. There were positive correlations between: TNFA, LEP and RETN with worse periodontal parameters; IL6, TNFA, ADIPOR1, LEP and RETN with waist-to-hip ratio; glycemic parameters with RETN; total cholesterol and triglycerides with LEP expression. We conclude that pro-inflammatory cytokines were related with worse lipid, glycemic and periodontal parameters, reinforcing that a hyper-inflammatory status connects systemic and oral inflammatory diseases.